A Marketing Mix Strategy to Improve the Marketing Performance on Tourist Destination of Wisata Minggon Jatinan at Hutan Rajawali in Batang (Universitas Negeri Semarang, 2022)
The aim of this study is to describe and analyze a marketing strategy. It is a qualitative research study. The data were collected by using observation and interview with descriptive analysis. The data collection method was using observation, interview, and documentation. The data validity technique used in this study was data triangulation techniques, a triangulation of sources and techniques. The analysis method used a descriptive analysis to describe and analyze the strategy marketing in marketing mix strategy on the tourist destination of Minggon Jatinan. Results of the study showed that based on the descriptive analysis and 4P mix strategy, the marketing strategy at tourist destination of Minggon Jatinan to improve the marketing performance has been maximum. Product of the tourist destination, especially traditional culinary specialties can improve the marketing performance. Price of the Minggon Jatinan is a subsidy from the local government of Batang so that this destination is free and equipped with cheap culinary choices which can improve the marketing performance. Place of this destination which is reachable in the center of the city with a leafy atmosphere can improve the marketing performance. The promotion used social media and conducting some events and challenges can improve the marketing performance.